X-Ray and Infrared Analysis on a Faint Polar RX J1745.5-2905 - Qishan Wang; Xiaohui Fang; Shengbang Qian (The Astrophysical Journal)
RX J1745.5-2905 is a faint and distant polar below the period gap. It was observed intensively in X-ray by Chandra, and its X-ray data reveal frequent brightness transitions between low and high states like we found in the prototype star AM Her. The X-ray radiation is consistent with a typical depiction of magnetic accretion. Although it was detected in X-rays, its counterpart in other bands has not been observed so far. We retrieved all public data and found that Hubble Space Telescope (HST) cached RX J1745.5-2905 in the infrared band (F139M). The infrared photometry confirms its normal behaviors in the low-energy band. Our analysis indicates that the combination of Chandra and HST can help us reach far-distant polars and that the long-term behavior of X-ray sources can help us identify the nature of these sources in the Galactic center.